Implementasi Program Gerakan Literasi Sekolah Studi Multi Situs di Sekolah Dasar - K, Putri Halimaini; Salminawati, Salminawati; Dahlan, Zaini (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
This study investigates the implementation of the School Literacy Movement (GLS) in two Islamic integrated elementary schools SDIT Madani and SDIT Rabbani in Aceh Tenggara, Indonesia. It aims to analyze the planning, execution, and contextual factors that support or hinder the sustainability of GLS in both institutions. Employing a qualitative multi-site case study design, data were collected through semi-structured interviews, participant observations, and document analysis. The findings reveal distinct literacy models: SDIT Madani incorporates literacy within tahfizh-based routines and promotes structured individual reading, while SDIT Rabbani adopts a thematic, community-centered literacy approach conducted in outdoor settings. Supporting factors include leadership commitment, teacher engagement, and stakeholder collaboration, whereas key barriers involve limited instructional time, insufficient resources, and lack of diverse reading materials. This study contributes to the discourse on localized literacy models in faith-based schools and recommends the development of school-based literacy forums, ongoing professional development for teachers, systematic parental engagement, and the integration of digital literacy tools to enhance program impact and sustainability.